2018
DOI: 10.1002/joc.5819
|View full text |Cite
|
Sign up to set email alerts
|

Extreme rainfall estimation at ungauged sites: Comparison between region‐of‐influence approach of regional analysis and spatial interpolation technique

Abstract: Reliable estimation of design extreme rainfall at an ungauged site is regarded to be an important task in engineering hydrology. This study compares two approaches of extreme rainfall estimation at ungauged locations: region-of-influence (ROI) approach of regional estimation and interpolation-based at-site estimation in a lowlying country where the density of rainfall measurements is relatively low. Both approaches incorporate generalized extreme value (GEV) based index-flood estimation procedure in which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…As a quality control procedure, the infilling of missing records was done using the Inverse Distance Weighted (IDW) interpolation technique developed by Shepard [66] in equation (1). Due to its robustness, the IDW technique has been applied in several studies [67][68][69][70][71]. e missing rainfall depth/intensity R M at station M for a given period was determined using rainfall values R j at the neighbouring stations q of the same period: 1.…”
Section: Rainfall and Potential Evapotranspiration Datamentioning
confidence: 99%
“…As a quality control procedure, the infilling of missing records was done using the Inverse Distance Weighted (IDW) interpolation technique developed by Shepard [66] in equation (1). Due to its robustness, the IDW technique has been applied in several studies [67][68][69][70][71]. e missing rainfall depth/intensity R M at station M for a given period was determined using rainfall values R j at the neighbouring stations q of the same period: 1.…”
Section: Rainfall and Potential Evapotranspiration Datamentioning
confidence: 99%
“…There are 28 observational stations of BMD within the study area of about 147,000 km 2 . Daily rainfall monitored at all 28 gauges of BMD successfully passed the homogeneity test by various literatures [32][33][34][35]. Notably, for all 28 BMD stations Khan et al [34] found almost straight lines with no breakpoint in the double mass curves and Mahmud et al [35] observed homogenous using Standard Normal Homogeneity test, Von Neumann Ratio test, Buishand Range test and Pettitt test.…”
Section: Study Area Methodology and Datamentioning
confidence: 65%
“…Further, the ROI approach (e.g., FEH) lacks the physical basis in the pooling of gauges that is provided by specifically accounting for the spatial variability of precipitation extremes and its driving variables. Various studies have reported that using a fixed regions approach to estimate extreme precipitation return levels provides more precise results with smaller errors compared to using ROI, and efficiently reduce random and climatologically irrelevant variations in estimating model parameters and high quantiles (Kyselý et al, 2011;Carreau et al, 2012;Das, 2019). Furthermore, Kyselý et al (2011) reported that using the at-site estimation approach to estimate extreme precipitation may be significantly affected by the inclusion of a single (outlying) observation, where the estimates would be uncertain.…”
Section: Discussionmentioning
confidence: 99%